Preference of Self-Initiates to Organize Repair in Improving EFL Students’ English Comprehension - Putri, Sonia Melani; Laila, Malikatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Language acquisition depends a lot on communication, especially on ena-bling pupils effectively convey knowledge and ideas. With an eye toward both listening and speaking abilities among students, this study aims to iden-tify and elaborate the use of repair in the classroom activity. Methodology: The study using a descriptive qualitative approach will see how repair tech-niques and cooperative learning are applied in classroom interactions. The study focuses specifically on 10th grade students at SMA Muhammadiyah 3 Surakarta. This study examined spoken language and how students handle daily interactions. The data will be gathered by means of observation, voice recordings, and expert judgement. Results: The researcher will further document numerous repair patterns in student in-teractions to evaluate how they affect understanding improvement. The re-sult shows that self-initiated self-repair was the most used strategy to im-prove EFL student English comprehension in classroom interactions as much as 47%, followed by other-initiated self-repair (30%), and other-initiated other-repair (23%). Applications/Originality/Value: The study offers insight into how teachers and students can improve com-munication and comprehension in English learning environments. In addi-tion, this study also addresses a gap in the literature and provides practical implications for improving EFL Students’ understanding using repair strategies.